Penentuan Nilai Kalor Serta Pengaruh Asam Klorida (Hcl) Terhadap Kadar Bioetanol Bonggol Pisang (Musa Paradisiacal) - Saleh, Asri; Saokani, Jawiana; Rijal, Samsul (Al-Kimia, 2016)
The research of influence bioetanol degree to chlorine acid catalyst concentration (HCl) in the hydrolysis process banana’s bump (Musa paradisiacal) has the goal to know the influence of catalyst concentration variation HCl was given the result of banana’s bump hydrolysis which maximum on catalyst variation HCl 0,5 M; 1,0 M; 1,5 M; 2,0 M and 2,5 M on temperature 70oC, 150 rpm during 120 minute with appointment of calor percentage on optimum etanol degree. Based on the result of the research etanol degree highest on HCl with concentration 2,5 with bioetanol degree 5.29% per 10 gram banana’s bump. Based on the ANAVA calculation found out F calculate < F table so that H0 accepted and H1 refused. It’s mean that there were not influenced of concentration HCl to bioetanol degree significantly. Percentage of bioetanol calor which found out on concentration HC1 2,5 M (maximum concentration) were 3461 (Sample I) and 3384 kkal (Sample II).